Historical and archaeological perspectives on the Itzas of Petén, Guatemala - Rice, Prudence M., editor; Rice, Don S., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
A detailed and thorough account of the Itzas--a Maya group that dominated much of the west lowland area of Petén, Guatemala. A theoretical perspective on the origins and an overview of the social, political, linguistic, and environmental history revealed in recent surveys and excavations.--Provided by publisher.
Part I. Cultural and Environmental Perspectives. 1. Introduction: The Itza Mayas and the Petén Itza Mayas, Their Environments and Their Neighbors; The Maya Lowlands: Environmental Perspectives; Who Were the Itzas? Etymological Perspectives; The Itzas of Petén; The Itzas of the Northern Lowlands and Their Allies -- 2. Itzaj Maya from a Historical Perspective; Yukateko versus Southern Yukatekan Language Varieties; Itzaj and Mopan; Contact with Ch'olan Languages; Concluding Discussion -- 3. The Lake Petén Itzá Watershed; Geology and Modern Ecology; Modern Limnology; Lacustrine Flora and Fauna; Historical Ecology; Climate Change; Summary -- Part II. Theoretical Perspectives on the Epiclassic Itzas: Factions, Migrations, Origins, and Texts. 4. Theoretical Contexts; Migration: Travel Tropes and Mobility Memes; Identities; Factions and Factionalism; Spatiality -- 5. Itza Origins; The Books of the Chilam Balam; Some Previous Reconstructions of Itza Origins; Concluding Thoughts -- 6. Lowland Maya Epiclassic Migrations; Western Lowlands; Southwestern Petén; Central Petén Lakes Region Eastern Petén, Belize, and the Southeast Northern Lowlands; Rethinking Epiclassic Migrations and the Itzas -- 7. Epiclassic Material Perspectives on the Itzas; Material Data and Identities; "Reassembling" the Itzas and Epiclassic Migrations; Concluding Thoughts -- Part III. Spanish Perspectives: Contact and Conquest "de paz y de paso". 8. Spanish Contacts and Conquest of Tayza; Early Spanish Colonial Institutions; First Spanish Encounter: Hernán Cortés; Sixteenth-Seventeenth Centuries: Attempts at Evangelization and Subjugation; 1695-96: Military Efforts and Road-Building; 1697: Ursúa's Final Conquest -- 9. Deconstructing Avendaño; Fray Avendaño and His Relación; Avendaño's Relación: Entering Itza Territory; Comparison: Hernáen Cortés 1525 Entrada; Deconstructing Avendaño's Account: Comparing Entradas; Avendaño's Relación: Departing Tayza; Where Was Alain/Yalain?; Concluding Thoughts -- 10. Knowing the Other; European Maps and Mapmaking; Avendaño's Map: Caveats and Conventions; The Periphery: Descriptions, Ethnopolities, and Toponyms; "Laguna del Ytzá como lo vi" -- Part IV. Material Perspectives: Postclassic and Contact-Period Archaeology and Artifacts. 11. Postclassic Pottery and Identities; The Petén Postclassic: Early Archaeology and Ceramic Studies; Postclassic Ceramic Wares, Groups, Types, and Forms; Contact- and Colonial-Period Pottery; Pottery Production and Contexts; Concluding Thoughts -- 12 Postclassic Architectural Traditions and the Petén Itzas; Building Elements; Types of Constructions; Architectural Assemblages; Summary -- 13. Small Projectile Points of Petén; Factions in the Lakes Region; Small Point Weaponry; Methods.
Keywords: Itza Indians -- Guatemala -- Petén (Department) -- Antiquities; Archaeology and history -- Guatemala -- Petén (Department); Excavations (Archaeology) -- Guatemala -- Petén (Department); Petén (Guatemala : Department) -- Antiquities